New distributional record of the endemic Red Sea Parrotfish Scarus collana (Rüppell, 1835) from the southern coast of India - Mohanraj, T.; Rajathy, T. Jebarani; Kumar, T.t. Ajith (Zootaxa, 2025)
This study presents the first recorded occurrence of the endemic Red Sea parrotfish, Scarus collana (Rüppell, 1835), in Indian waters. The specimen was collected through trap fishing in the reef and paar regions of the Gulf of Mannar. The specimens were measured 10.8–34.2 cm in length (TL) and weighed 232–1248 g. This newly recorded endemic species of Red Sea represents a geographic range extension and contributes to the marine biodiversity records of India.